Professional training of farm managers: Analysis of trends and current status - Rusu Marioara (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 14th Edition, 2023)
In recent years, worldwide, increasing the professional training of farm managers has become vital in the context of the implementation of new technologies/production methods: professional training is a key component needed to face current and future challenges. New technologies, which pave the way for greater efficiency in the agricultural sector, require farm managers to acquire new skills such as data analysis, robotics, GPS systems, drone operation, etc. Acquiring the right mixture of knowledge will increase understanding of precision farming techniques and strengthen farm sustainability. Romanian agriculture must rally along this path in order to become more sustainable - while meeting the increasingly high expectations of consumers. The main objective followed in this paper is the analysis of the structure of Romanian farm managers according to the degree of professional training. The methods used to achieve this objective were the documentary analysis of the works published in the country and abroad on this subject and the statistical analysis that used data collected during the Agricultural Censuses. The main conclusion that emerges shows that in the last ten years the level of professional training of farm heads was quite low, representing one of the main factors that led to maintaining a low competitiveness of the agricultural sector.
Keywords: Q19; 330; professional agricultural training; farm manager; Romania